2010
DOI: 10.1111/j.1567-1364.2010.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast species composition differs between artisan bakery and spontaneous laboratory sourdoughs

Abstract: Sourdough fermentations are characterized by the combined activity of lactic acid bacteria and yeasts. An investigation of the microbial composition of 21 artisan sourdoughs from 11 different Belgian bakeries yielded 127 yeast isolates. Also, 12 spontaneous 10-day laboratory sourdough fermentations with daily backslopping were performed with rye, wheat, and spelt flour, resulting in the isolation of 217 yeast colonies. The isolates were grouped according to PCR-fingerprints obtained with the primer M13. Repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 41 publications
5
79
3
Order By: Relevance
“…These results were in agreement with previous studies on sourdoughs from the center and south of Italy (31,39). The dominance of a few strains of S. cerevisiae can be related to contamination by baker's yeast (45). The dominance of C. humilis has been shown in Pagnotta del Dittaino PDO sourdough (21).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results were in agreement with previous studies on sourdoughs from the center and south of Italy (31,39). The dominance of a few strains of S. cerevisiae can be related to contamination by baker's yeast (45). The dominance of C. humilis has been shown in Pagnotta del Dittaino PDO sourdough (21).…”
Section: Discussionsupporting
confidence: 82%
“…K. barnettii and K. exigua were isolated only from Pane nero di Castelvetrano sourdough. K. exigua has previously been isolated from a number of sourdoughs (16), whereas the presence of K. barnettii in wheat sourdoughs is reported only in one previous paper (45).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the L. sanfranciscensis-C. humilis association, associations of Saccharomyces cerevisiae and L. plantarum, Candida spp. and L. brevis, and Kazachstania barnettii and L. sanfranciscensis have been reported too (4,27,55). Furthermore, sourdough continues to be a source of unexplored LAB species diversity, as exemplified by the continuous reporting of new LAB species (11).…”
mentioning
confidence: 99%
“…This demonstrates the large microbial diversity present in sourdough. Moreover, since these species are mostly isolated in exploratory studies of a limited number of fermentations, it remains a challenge to know what the exact reasons are why one species should be dominant over another or present in one sourdough environment and not in another.In previous studies, it has been shown that type I sourdough fermentations carried out in the laboratory with flour as the sole nonsterile ingredient harbor a different species diversity than artisan sourdoughs prepared in a bakery, with respect to both LAB and yeast species (42,43,49,55,57,58). Laboratory sourdoughs based on wheat, rye, or spelt, daily backslopped for…”
mentioning
confidence: 99%
See 1 more Smart Citation